2016
DOI: 10.1186/s40064-016-1883-4
|View full text |Cite
|
Sign up to set email alerts
|

Rural settlements dynamics and the prospects of densification strategy in rural Bangladesh

Abstract: Given the year on year decrease of rural farmland and various forms of land degradation through the intrusion of non-farm land uses, the government of Bangladesh has drafted the agrarian reform strategies, primarily to protect the agricultural land from encroachment, conversion, and indiscriminate use. The draft Agricultural Land Protection and Land Use Bill since its inception in 2011 is facing serious uncertainties of implementation due to its borrowed nature from the developed contexts and inadequacy to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…ere is a significant correlation and interaction between the external natural environmental factors represented by regional location and the economic and social development factors represented by farmers' per capita income. e natural environmental factors have a great influence on the evolution of the rural settlement form and last for a long time [6,7]. Due to the urbanization factors, the production and life of rural settlements are affected, which accelerates the evolution of the form and scale of rural settlements.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…ere is a significant correlation and interaction between the external natural environmental factors represented by regional location and the economic and social development factors represented by farmers' per capita income. e natural environmental factors have a great influence on the evolution of the rural settlement form and last for a long time [6,7]. Due to the urbanization factors, the production and life of rural settlements are affected, which accelerates the evolution of the form and scale of rural settlements.…”
Section: Results and Analysismentioning
confidence: 99%
“…From the research status and future development trend of rural geography, some scholars in the United States and Britain analyzed the geography, history, and their relationship with rural settlement areas, and explored the relationship between rural settlement morphological structure adjustment, economic and social development, and landscape change in the industrial age [7,8]. In addition, some scholars have studied the relationship between the morphological structure of rural settlements and other adjacent disciplines.…”
Section: Related Workmentioning
confidence: 99%
“…In Bangladesh, agricultural lands are mostly owned by small-scale farmers; thus, it is comparatively inexpensive and easy to convert land to non-agricultural purposes. Studies have also found that the land ownership size of a household and the non-agricultural occupation of heads of households were the two primary reasons for agricultural land transformation, resulting in declines in agrarian income and productivity (Quasem 2011 (Alam et al 2016). Although these historical land policies emphasize the conservation of agricultural lands and limit their transformation to non-farming purposes, they leave room for flexibility, which has caused the policies to be ineffective (LANDac 2016).…”
Section: Distance From Agricultural Landsmentioning
confidence: 99%
“…Clearly, this development represents a serious threat to regional food security and sustainable development. It has been reported that urban expansion usually leads to the loss of high-quality arable land because the distribution of urban areas and high-quality arable land usually shares similar land conditions such as the flat terrain and having resources close to the water [2,4,11,12,23,38,39,42,44,45]. However, whether rural settlement expansion prefers to consume high-quality arable land is still not clear now.…”
Section: Introductionmentioning
confidence: 99%